Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1111/j.1469-8986.1997.tb02415.x
|View full text |Cite
|
Sign up to set email alerts
|

P300 event‐related potential heritability in monozygotic and dizygotic twins

Abstract: The present study examined the heritability of the P3 waveform and the N1, P2, and N2 components by assessing the visual event-related potential (ERP) of 30 monozygotic (MZ) and 34 dizygotic (DZ) twin pairs. Electroencephalogram activity was recorded from Pz, P3, and P4 scalp sites while individuals performed a reaction time task involving two conditions differing in difficulty. Genetic modeling indicated substantial genetic influence on P3 amplitude, P3 latency, and manual reaction time for the difficult cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
4
8

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 26 publications
10
96
4
8
Order By: Relevance
“…This contrasts with the results of two other large twin studies on P3 that did not find evidence for heritability of P3 latency in adults or adolescents (O'Connor et al, 1994;van Beijsterveldt, 1996). A reason for this discrepancy is provided by the study of Katsanis et al (1997). In that study, P3 latency was found to be influenced by genetic factors in the difficult visual oddball task, but not in the easy visual oddball task.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This contrasts with the results of two other large twin studies on P3 that did not find evidence for heritability of P3 latency in adults or adolescents (O'Connor et al, 1994;van Beijsterveldt, 1996). A reason for this discrepancy is provided by the study of Katsanis et al (1997). In that study, P3 latency was found to be influenced by genetic factors in the difficult visual oddball task, but not in the easy visual oddball task.…”
Section: Discussioncontrasting
confidence: 55%
“…No genetic influences on P3 latencies were observed. Recently, Katsanis, Iacono, McGue, and Carlson (1997) reported on a P3 study in 64 adolescent MZ and DZ twin pairs. The study included an easy and a difficult visual oddball task.…”
mentioning
confidence: 99%
“…EEG spectral characteristics are highly similar for identical twins (Lykken, 1974;Stassen et al, 1987), and strong spectral power similarities are observed for biological family members (Eischen et al, 1995;Vogel et al, 1979). P300 is virtually identical for pairs of monozygotic twins, less so for dyzygotic twins, and different for unrelated controls (Katsanis et al, 1997;O'Connor et al, 1994;Polich and Burns, 1987). P300 heritability also is evidenced by biologically related family members who demonstrate significant inter-family member correlations for ERP measures Polich and Bloom, 1999).…”
Section: Applied P300 Characteristicsmentioning
confidence: 97%
“…It is therefore not surprising that P300 characteristics have been found to be strikingly similar between pairs of monozygotic as compared to dyzygotic twins or unrelated controls (Polich and Burns, 1987;O'Connor et al, 1994;Katsanis et al, 1997). Meta-analyses of twin studies (van Beijsterveldt and van Baal, Page 9 2002) estimated P300 amplitude heritability to be 60%, with a more recent twin study (Hall et al, 2006) yielding a somewhat higher estimate of 69%.…”
Section: Genetic Contributions To P300mentioning
confidence: 99%